The Influence of Work Motivation, Job Satisfaction and Democratic Leadership on Teacher Performance - Safrida Safrida; Hendy Tannady; Muh. Rezky Naim; Joko Ariawan; Deddy Novie Citra Arta (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Many countries recognize that the problem of education is complicated, but everyone feels that education is an important state duty. In developing countries such as Indonesia, existing education systems and methods are often the target of criticism because the entire education system is in doubt. The low quality of education in Indonesia today will certainly have a negative impact on the life of the nation, because one of the factors for the progress of a country is the advancement of education in that country. Therefore, the purpose of this research is to explain and understand the influence of democratic leadership, work motivation, and job satisfaction on teachers in school. The study was conducted using a survey by distributing questionnaires in April 2022, in which 50 School teachers were used as respondents. The results of this study indicate that high democratic leadership will improve teacher performance, high work motivation will improve teacher performance, and good job satisfaction will improve teacher performance. Simultaneously, the democratic leadership variable, work motivation variable, and job satisfaction variable proved to have a positive and significant effect on teacher performance at school.